2019
DOI: 10.3390/cosmetics6030042
|View full text |Cite
|
Sign up to set email alerts
|

Topical Sunscreen Application Preventing Skin Cancer: Systematic Review

Abstract: Background: Avoiding extended exposure to direct sunlight and the topical application of sunscreen when exposed are the main techniques used to protect the skin form sunburn, photoaging, and skin cancer risk (melanoma and non-melanoma skin cancer). Preventive strategies could lead to a significant reduction of the excessive health system cost for the treatment of these conditions. Sunscreen employment and efficacy stay controversial despite decades of humane use with health benefits closely related. At the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…The use of sunscreen is an important strategy protecting against UVR from sunlight exposure [ 30 ]. Sunscreen attenuates the effects of UVR on the skin, mainly as UVR is absorbed by chemical filters including para-aminobenzoic acid (PABA) derivatives, benzophenones and salycilates [ 31 ]. These organic compounds substantially interfere with the skin production of vitamin D3 [ 32 ].…”
Section: Vitamin D Sourcesmentioning
confidence: 99%
“…The use of sunscreen is an important strategy protecting against UVR from sunlight exposure [ 30 ]. Sunscreen attenuates the effects of UVR on the skin, mainly as UVR is absorbed by chemical filters including para-aminobenzoic acid (PABA) derivatives, benzophenones and salycilates [ 31 ]. These organic compounds substantially interfere with the skin production of vitamin D3 [ 32 ].…”
Section: Vitamin D Sourcesmentioning
confidence: 99%
“…New FDA recommendations try to overcome these deficits by regulations of usage and selling of the creams ( 41 ). Recently, it was observed that it does not protect against BCC, but it protects against actinic keratosis and squamous cell carcinoma ( 42 ). A large cohort study reports that use of high SPF cream before the age of 25, but not after, protects against BCC ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used sun protection for skin are sunscreens, which have been proven to reduce sunburns, skin ageing, and skin cancer risk (melanoma and non‐melanoma) through their ability to reflect, scatter and/or absorb UV light. [ 7,8 ] Sunscreens exist in many types of formulations such as emulsions, gels, aerosols, and sticks, and their active ingredients include inorganic and organic UV filters—which are the most commonly applied filter types [ 9 ] —as well as hybrid and botanical ingredients. [ 10 ] It was previously believed that inorganic filters (physical filters), which include titanium dioxide and zinc oxide particles, worked solely by reflecting and scattering the UV rays before they reach the skin.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Inorganic filters must be able to block UV light over the entire UVA/UVB range (290–400 nm), and their ability to reflect and scatter UV rays depends on their intrinsic refractive indexes, particle size, and dispersion in the emulsion. [ 7,12 ]…”
Section: Introductionmentioning
confidence: 99%